An efficient wide input wide output CrCM flyback converter in high‐power LED lighting. (1st May 2020) - Pal, Somnath; Singh, Bhim; Shrivastava, Ashish
Summary: This paper deals with a power factor corrected (PFC) flyback converter for high‐power light emitting diode lighting applications. This flyback converter is designed to operate in critical conduction mode to achieve improved power quality at universal AC mains and high efficiency with the low component count. The converter is analyzed using state‐space analysis with closed‐loop stability under varying input and output conditions. The PFC converter is designed and implemented with wide input and wide output variations. The performance of the prototype is also investigated for improved power quality such as power factor and harmonics distortion of AC mains current at universal AC mains of 85 to 265 V. The achieved efficiency of this converter is 92% and total harmonic distortion is less than 6% over universal AC mains for a prototype of 100 W, which are much improved results as compared to discontinuous conduction mode operation of the same converter.